Políticas migratórias de proteção aos migrantes e retornados hondurenhos : 2017-2019 - Galdámez, Norman Roy Estrada (2020)
This research presents an analysis of migrants’ protection policy and migrants returned to Honduran, specifically migrants returned in the years 2017-2019 from the United States and Mexico, years in which migration movements increased. Facing the exodus of returnees, the Honduran government through the foreign affairs secretariat decides to adopt the Law on the protection of Honduran migrants and their families as a measure to resolve the exodus of migrants. In order to understand better the policies for the protection of migrants and Honduran returnees, a qualitative methodology is applied to analyze the data provided by the Honduras Consular Observatory and international agencies. In addition, other sources were consulted to define some concepts which are presented in this research. With this research on protection policies, it was stated the type of assistance that Honduran returnees receive and that helps solve part of the problems of those who return.